Long-term outcomes of conservative treatment and endovascular treatment in patients with symptomatic spontaneous isolated superior mesenteric artery dissection: a single-center experience - Xu, Leyin; Shao, Jiang; Zhang, Daming; Qiu, Chenyang; Wang, Jingjing; Li, Kang; Fang, Lijing; Zhang, Xin; Lei, Jinsong; Lai, Zhichao; Ma, Jiangyu; Yu, Yanying; et al. (BMC cardiovascular disorders, 2020)
Spontaneous isolated superior mesenteric artery dissection (SISMAD) is a rare vascular disorder, and the treatment strategies remain controversial. This study aimed to compare outcomes of conservative and endovascular treatments in symptomatic patients with SISMAD. Forty-two consecutive SISMAD patients who were admitted to a single center between October 2009 and May 2018 were enrolled in this study. Based on their symptoms, 15 had conservative treatment, and 27 had endovascular treatment. The baseline characteristics, treatments, and follow-up results of the conservative group and endovascular group were analysed. The rates of symptom relief were 93.3% in the conservative group and 96.3% in the endovascular group. The procedure-related complications in the endovascular group included one case of pseudoaneurysm formation in the left brachial artery. During the follow-up period (median 28.5 months), a higher proportion of patients in the conservative group had symptom recurrence (42.9% in the conservative group versus 4.8% in the endovascular group, p < 0.001). Four patients in the conservative group and one patient in the endovascular group had additional endovascular intervention during follow-up. Compared with the conservative group, patients in the endovascular group had statistically significantly longer symptom-free survival (p = 0.014) and a higher rate of superior mesenteric artery (SMA) remodeling (p < 0.001). For symptomatic SISMAD, endovascularly treated patients had a lower rate of symptom recurrence and a higher rate of SMA remodeling in the long term. Prospective, multi-center studies are needed to confirm the long-term outcomes of both treatments.